2015
DOI: 10.7554/elife.10616
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular sphingosine releases calcium from lysosomes

Abstract: To elucidate new functions of sphingosine (Sph), we demonstrate that the spontaneous elevation of intracellular Sph levels via caged Sph leads to a significant and transient calcium release from acidic stores that is independent of sphingosine 1-phosphate, extracellular and ER calcium levels. This photo-induced Sph-driven calcium release requires the two-pore channel 1 (TPC1) residing on endosomes and lysosomes. Further, uncaging of Sph leads to the translocation of the autophagy-relevant transcription factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
136
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(157 citation statements)
references
References 80 publications
(99 reference statements)
9
136
1
11
Order By: Relevance
“…Transcription factor EB (TFEB) is a master regulator of autophagy and lysosome-associated genes (Settembre and Medina, 2015). As lysosomal Sph can activate TFEB (Höglinger et al, 2015), we examined TFEB localization during the clearance of SK1-I-induced vacuoles. Indeed, TFEB translocates to the nucleus prior to vacuole clearance (Figures 7A and 7B).…”
Section: Resultsmentioning
confidence: 99%
“…Transcription factor EB (TFEB) is a master regulator of autophagy and lysosome-associated genes (Settembre and Medina, 2015). As lysosomal Sph can activate TFEB (Höglinger et al, 2015), we examined TFEB localization during the clearance of SK1-I-induced vacuoles. Indeed, TFEB translocates to the nucleus prior to vacuole clearance (Figures 7A and 7B).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that sphingosine generation within lysosomes also mediates lysosomal permeability and compromises lysosomal integrity [55, 56]. It is certainly possible that S. aureus α-toxin does not only activate the acid sphingomyelinase, but also the acid ceramidase, and thereby triggers the formation of ceramide and sphingosine.…”
Section: Discussionmentioning
confidence: 99%
“…Since ceramides produced in the lysosome by ASM are not shuttled to other subcellular compartments, they may directly influence the coalescence of microdomains required for lysosomal signaling (7). However, ASM forms a molecular complex with acid ceramidase, which metabolizes ceramide to sphingosine, a molecule itself implicated in autophagy via alterations of lysosomal calcium efflux (8). We investigated if ASM is required for LYNUS function of by guest, on www.jlr.org Downloaded from inhibition of autophagy during homeostatic conditions, hypothesizing that inhibition of ASM is sufficient to trigger autophagy associated with disrupted LYNUS signaling.…”
Section: Introductionmentioning
confidence: 99%